HBR's 10 must reads on Strategy (Harvard Business Review Press, 2011)
This collection of best-selling articles includes: featured article "What Is Strategy?" by Michael E. Porter, "The Five Competitive Forces That Shape Strategy," "Building Your Company's Vision," "Reinventing Your Business Model," "Blue Ocean Strategy," "The Secrets to Successful Strategy Execution," "Using the Balanced Scorecard as a Strategic Management System," "Transforming Corner-Office Strategy into Frontline Action," "Turning Great Strategy into Great Performance," and "Who Has the D? How Clear Decision Roles Enhance Organizational Performance"